Lighting, scenography and staging: the paradigm change after Ziembinski's arrival in Brazil. (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2021)
This article reviews the history of brazilian lighting design, from the Portugueses invasion in 1500 to the present day, highlighting the importance of the 1940s, with the arrival of Ziembinski and other foreigners. It relates staging, with lighting design and scenography, especially after the change of paradigm, influenced by the foreigners who arrived here, fleeing the war. The relationship between several arts and politics were responsible for the creation of a national aesthetic, thus forming the Brazilian Modern Theater, being consolidated with the participation of Jorginho de Carvalho, a lighting designer from Rio de Janeiro. Through history books research, as well as third parties interviews, the author draws a relation between different areas of a theatrical spectacle, highlighting the staging of Wedding Dress, text by Nelson Rodrigues, staged by Ziembinski, in 1943.